Agricultural peatlands conservation: How does the addition of plant biomass and copper affect soil fertility?. Issue 4 (29th June 2021) - Bourdon, Karolane; Fortin, Josée; Dessureault‐Rompré, Jacynthe; Caron, Jean
Abstract: Subsidence, erosion, and degradation in agricultural peatlands are leading to the disappearance of highly fertile farmland. This study investigated two strategies aimed at extending the lifespan of cultivated peat soils: the application of straw and wood chips to compensate for soil losses and the application of copper (Cu) to slow peat decomposition, based on previous recommendations. Peat soil samples (270 g) were amended with 11 t ha –1 of biomass materials (14.8 g kg –1 ) and 235.6 mg Cu kg –1 and incubated in glass jars at constant temperature and water content. Thirty chemical parameters were then monitored over a 56‐d period through repeated soil sampling. Discriminant analysis showed that the addition of biomass had the greatest affect on nitrogen (N) availability, immobilizing 7.8 to 12.1 kg of inorganic N per metric ton of incorporated biomass. Considering that peat soils may require from 4 to 40 t biomass ha –1 yr –1 to reach carbon equilibrium, the tested biomass materials could immobilize from 34 to 500 kg ha –1 of N if confirmed at the field scale. This may help capture excess N but may also limit crop growth. Alternatively, slowing decomposition could reduce both biomass requirements and N immobilization. However, the results show that Cu had little effect on parameters linked to organic matter decomposition. Indeed, dissolved organic carbon was decreased by 11% in Cu‐treated soils. A longer‐term study should be conducted to confirm these observations at the field scale, thus helping to develop conservation strategies suitable for agricultural production. Core Ideas: Agricultural peatlands degradation lead to the disappearance of highly fertile land. Adding biomass with a high C/N ratio to peat soil could help conserve peat soils. N immobilization is the primary concern when adding C‐rich biomass to peat soil. C‐rich biomass could help capture excess N in peat soils. The effectiveness of copper in slowing peat soil decomposition seems uncertain.